Binge‐type eating disrupts dopaminergic and GABAergic signaling in the prefrontal cortex and ventral tegmental area. Issue 10 (25th August 2016) - Corwin, Rebecca L.W.; Wojnicki, Francis H.E.; Zimmer, Derek J.; Babbs, R. Keith; McGrath, Lauren E.; Olivos, Diana R.; Mietlicki‐Baase, Elizabeth G.; Hayes, Matthew R.
Abstract : Objective: Binge eating is characterized by repeated intermittent bouts of compulsive overconsumption of food. Treatment is challenging given limited understanding of the mechanisms underlying this type of disordered eating. The hypothesis that dysregulation of mesocortical dopaminergic and GABAergic systems underlie binge eating was tested. Methods: Analysis of gene expression within the ventral tegmental area and its terminal mesocortical regions was examined in bingeing rats before and after bingeing occurred. In addition, alterations in binge‐type behavior induced by pharmacological inactivation of subnuclei of the prefrontal cortex (PFC) and by pharmacological activation and inhibition of cortical D1 and D2 receptors were examined. Results: Correlative and functional evidence demonstrates dysregulated neurotransmitter processing by the PFC and ventral tegmental area, but not the amygdala or nucleus accumbens, in bingeing rats. Either GABAergic inactivation or D2‐like receptor activation within the PFC increased consumption in bingeing rats, but not controls, suggesting that the PFC, and D2 receptors in particular, functions as a behavioral brake to limit bingeing. Conclusions: The act of bingeing resolved some gene expression differences that preceded binge onset, further suggesting that bingeing may partially serve to self‐medicate a system driving this maladaptive behavior. However, the failure of bingeing to resolve other dopaminergic/GABAergic differences may render individuals vulnerable to future binge episodes.